Boosting Academic Resilience through Spiritual Well-being: A Study in Juvenile Prison in Indonesia - Saefudin, Wahyu; Sriwiyanti (Restorative : Journal of Indonesian Probation and Parole System, 2023)
A juvenile prison is a rehabilitative institution where one of its programs is designed to educate underaged offenders. The adolescent subsequently registered as a student and progressed through various grades. Unfortunately, during the education and rehabilitation process, juveniles experience adverse psychological states and encounter external difficulties. Therefore, the juveniles must have stress resistance or resilience to deal with these issues, as well as spiritual well-being which provides a holistic perspective on an individual's existence and facilitates a more comfortable understanding of life. This broad perspective empowers the individual to manage challenging conditions, including the educational environment. Therefore, this study assumed that spiritual well-being affects student academic resilience. Researchers employed the proportionate stratified random sampling approach. There were 100 juvenile respondents. The enrollment criteria include juveniles aged 12 to 18 who perpetrated various criminal offenses, served their sentences in prisons, and participated in the institution's educational program. The results are categorized into two principal findings discussions. First, the academic resilience of juveniles is found to be 75% high and 25% moderate. Second, spiritual well-being correlates with students' academic resilience, and the regression analysis results depict that spiritual well-being can explain 42.6% of academic resilience. These results indicate that spiritual well-being enhances academic resilience during study in prison. Abstrak. Lembaga Pembinaan Khusus Anak (LPKA) adalah lembaga rehabilitasi di mana salah satu programnya dirancang untuk mendidik anak yang berhadapan dengan hukum. Anak tersebut kemudian terdaftar sebagai siswa dan berkembang melalui berbagai tingkatan. Sayangnya, selama proses pendidikan dan rehabilitasi, para remaja mengalami kondisi psikologis yang buruk dan menghadapi kesulitan eksternal. Oleh karena itu, para remaja harus memiliki ketahanan atau ketangguhan terhadap stres untuk menghadapi masalah-masalah ini, serta kesejahteraan spiritual yang memberikan perspektif holistik tentang eksistensi individu dan memfasilitasi pemahaman yang lebih nyaman tentang kehidupan. Perspektif mengenai kesejahteraan spiritual ini memberdayakan individu untuk mengelola kondisi-kondisi yang menantang, termasuk dalam proses pendidikan. Oleh karena itu, penelitian ini mengasumsikan bahwa kesejahteraan spiritual memengaruhi resiliensi akademik siswa. Penelitian ini menggunakan pendekatan pemilihan sampel acak proporsional berstrata, dengan 100 responden. Kriteria responden meliputi Anak berusia 12 hingga 18 tahun yang melakukan berbagai tindak pidana, menjalani hukumannya di penjara, dan berpartisipasi dalam program pendidikan lembaga tersebut. Hasilnya dikategorikan menjadi dua diskusi utama. Pertama, ketahanan akademik para remaja ditemukan sebanyak 75% tinggi dan 25% sedang. Kedua, kesejahteraan spiritual berkorelasi dengan ketahanan akademik siswa, dari hasil analisis regresi menggambarkan bahwa kesejahteraan spiritual dapat menjelaskan 42,6% ketahanan akademik. Hasil ini menunjukkan bahwa kesejahteraan spiritual meningkatkan ketahanan akademik selama proses pendidikan di penjara. Keywords: resiliensi akademik, kesejahteraan spirirual, Lembaga Pembinaan Khusus Anak